2005
DOI: 10.1021/ol050897a
|View full text |Cite
|
Sign up to set email alerts
|

A Re(V)-Catalyzed C−N Bond-Forming Route to Human Lipoxygenase Inhibitors

Abstract: [reaction: see text] A regioselective synthesis of propargylamines by the coupling of propargyl alcohols with tosylamines and carbamates catalyzed by an air- and moisture-tolerant rhenium-oxo complex is described. The ability to couple functionalized components allows for convergent approaches to nitrogen-containing heterocyclic compounds such as the marine antibiotic pentabromopseudilin. These compounds were assayed against human lipoxygenase and found to be both potent and selective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(46 citation statements)
references
References 29 publications
3
41
0
1
Order By: Relevance
“…An iridium catalyzed N-allylation was used in a synthesis of (+)-and (−)-nicotine [681]. Rhenium catalyzed N-propargylation of amines with propargylic alcohols [682]. (92) Palladium catalyzed S-allylations of arenethiols [683] and of sodium phenylsulfinate [684] with allylic alcohols.…”
Section: Carbon-heteroatom Bond-forming Reactions Using Heteroatom Numentioning
confidence: 99%
“…An iridium catalyzed N-allylation was used in a synthesis of (+)-and (−)-nicotine [681]. Rhenium catalyzed N-propargylation of amines with propargylic alcohols [682]. (92) Palladium catalyzed S-allylations of arenethiols [683] and of sodium phenylsulfinate [684] with allylic alcohols.…”
Section: Carbon-heteroatom Bond-forming Reactions Using Heteroatom Numentioning
confidence: 99%
“…[5] Rhenium, gold, rhodium, and iron complexes were also reported recently to be effective catalysts for propargylic amination. [6] Remarkably, enantioselective examples of propargylic substitution reactions are rare, [7] and to our knowledge no asymmetric amination reaction has been reported to date. Inspired by the results of Murahashi and co-workers, we describe herein an enantioselective version of the copper-catalyzed propargylic amination of propargylic acetates.…”
mentioning
confidence: 97%
“…The synthesis of ligands 1 and 6-8 is well documented, and 6, in particular, was obtained readily in only two steps from commercially available compounds. [10] An optimization study with ligand 6 revealed that other copper salts, such as [Cu(CH 3 CN) 4 ]PF 6 , CuOTf·benzene, and Cu(OAc) 2 , gave similar results, although CuI was slightly superior with respect to the selectivity ( Table 2, entries 1-3). High enantioselectivity and a high reaction rate were only observed with polar protic solvents, the best results with [a] Reaction conditions: 9 a (0.20 mmol), o-anisidine (0.40 mmol), DIPEA (0.80 mmol), CuI (0.02 mmol), and the ligand (0.024 mmol) were stirred in methanol (2 mL) at 25 8C.…”
mentioning
confidence: 97%
“…It is also noteworthy that the desired products were obtained using tertiary-propargyl alcohols 6r and 6s. Previously reported propargylic amination catalysts were not applied to tertiary-propargyl alcohols, possibly due to a competitive dehydration reaction to afford enynes [34,35]. The addition of Drierite was essential to obtain products 7rf and 7sa in >60% yield (Table 12, entries 3 and 4).…”
Section: Direct Substitution Of the Hydroxy Group In Alcohols With Ammentioning
confidence: 99%